Penerapan Pembelajaran Sosial Emosional untuk Menciptakan Iklim Kelas Kondusif di SD Negeri Nyalindung 2: Penelitian - Enden Sirojudin; Hadiyanti; Tia Mutia; Yeni Nuraeni; Dinny Mardiana (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
This study investigates teachers’ strategies in implementing Social Emotional Learning (SEL) and examines its effects on classroom climate and students’ socio-emotional development in Grade VI of SD Negeri Nyalindung 2. Employing a qualitative descriptive design, the report is produced from examining files, questions and answers and observations. The results show that three key strategies—emotional reflection, collaborative learning, and jointly formulated classroom agreements—contributed to improved emotional regulation, empathy, interpersonal skills, and responsible decision-making among students. Moreover, the classroom climate became increasingly supportive and inclusive, characterized by reduced minor conflicts, greater openness in communication, and more positive peer interactions. These findings highlight the pedagogical significance of integrating Social Emotional Learning into classroom practice, suggesting that Social Emotional Learning fosters not only individual socio-emotional competencies but also a psychologically safe learning environment that enhances students’ engagement. Overall, Social Emotional Learning constitutes an essential instructional approach for promoting students’ socio-emotional well-being and strengthening character formation in primary education.